An exploration of the extent of inclusion of spirituality and spiritual care concepts in core nursing textbooks - SHEAF, GREG; MURPHY, MARYANNE; BEGLEY, THELMA; NEILL, FREDA; TIMMINS, FIONA (My University, 2015)
Holistic care that encompasses a spiritual dimension is an expectation in modern healthcare (Rothman, 2009). Increasing attention is being paid to the role of nurses in providing spiritual care to patients. However nurses lack specific skills and expertise in this area (Lundmark, 2006; Timmins, 2010; RCN, 2011), and the extent to which their undergraduate education prepares them for this role is unclear. There is often an absence of clear direction about what to teach undergraduate nursing students. The extent to which core textbooks direct student studies in this area is not known. There is some evidence that some of these fundamental core textbooks provide insufficient direction (Pesut, 2008), thus gaps in knowledge and care provision in this field could be exacerbated. Aim The aim of this study is to examine the extent to which spiritual care concepts are addressed in core nursing textbooks. Methods Five hundred and forty three books were sampled from the Nursing and Midwifery Core Collection list (UK) (Tomlinsons, 2010) representing 94% of the total (n = 580). A survey, the Spirituality Textbook Analysis Tool (STAT), was developed and used to collect data. Findings One hundred and thirty of the books included content related to spirituality and religion. However there was little consistency in the core nursing textbooks with regard to direction for providing spiritual care. Thirty eight percent of the books defined spiritual care and 36% provided an outline of the role of the nurse in providing this. While some books advocated the assessment of patients' spiritual needs (32%) few referred specifically to assessment tools. Discussion It is essential that nurses are adequately prepared to address the spiritual needs of patients. While there are numerous spiritual care texts that deal solely with this issue for nurses, there is an argument emerging that core nursing texts used by nursing students ought to encompass spiritual care elements. Lack of specific focus on this field, by these key textbooks might infer that this important element of holistic care is less important than other matters in nursing. True holistic care ought to permeate across textbooks and as such spirituality and spiritual care ought not to be sequestered to specialised texts. Core nursing texts need to be strengthened through consistency of application and inclusion of spirituality and spiritual care where relevant.
PUBLISHED
Keywords: Assessment; Spiritual; Spiritual care; Nursing student; Textbook; Identities in Transformation